Lithium Toxicity and Neurologic Effects: Probable Neuroleptic Malignant Syndrome Resulting from Lithium Toxicity - Osamede Edokpolo; Madiha Fyyaz (Case Reports in Psychiatry)
Introduction. We present the case of a patient who developed lithium toxicity with normal therapeutic levels, as a result of pharmacokinetic interaction with Valsartan, and probable Neuroleptic Malignant Syndrome from the ensuing lithium toxicity. Case Presentation. A 59-year old black male with bipolar disorder maintained on lithium and fluphenazine therapy presented with a 2 week history of worsening confusion, tremor, and gait abnormality. He recently had his dose of Valsartan increased. At presentation, patient had signs of autonomic instability, he was confused, dehydrated, and had rigidity of upper extremities. Significant labs on admission were lithium level-1.2, elevated CK-6008, leukocytosis WBC-22, and renal impairment; Creatinine-4.1, BUN-35, HCO3-20.1, and blood glucose 145. CT/MRI brain showed old cerebral infarcts, and there was no evidence of an infective process. Lithium and fluphenazine were discontinued, his lithium levels gradually decreased, and he improved with supportive treatment including rehydration and correction of electrolyte imbalance. Conclusions. This case illustrates that lithium toxicity can occur within therapeutic levels, and the neurotoxic effect of lithium can include Neuroleptic Malignant Syndrome. Clinicians should be aware of the risk associated with drug interactions with lithium.